PERAN PEBANKAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Ilhamdi, Ilhamdi (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2020)
This study aims to determine the role of Islamic banking on economic growth in Indonesia and to compared it with conventional banks. In recent years, Islamic banking has increased in terms of assets. By using panel data regression, this study examines the effect of Islamic banking on economic growth. Besides that, how big is the level of elasticity to economic growth. This study uses secondary data in the form of Gross Domestic Product (GDP), Islamic banking financing and credit by conventional banks. The results showed that Islamic banking and conventional banks had a positive impact on economic growth with the level of elasticity of Islamic banking still below conventional banks. So the existence of Islamic and conventional banks does not always replace, but complement each other in Indonesia.